Incorporation of new employees with recognised disabilities in a spanish bank last year: A cross-sectional study - Reinoso-Barbero, Luis; Muñoz-Dueñas, Pilar; Abril, Isabella; Álvarez-Llergo, Azahara; Gómez-Paredes, Laura; Muñoz-Gutiérrez, Juan; Pérez-Herreras, Cristina; Gómez-Gallego, Félix; Catalán-Mejía, Gema; Mazo, Rafael; Corral, Octavio (WORK: A Journal of Prevention, Assessment & Rehabilitation, 2026)
Background Spanish companies with ≥50 employees must have ≥2% of their workforce with a recognised disability. Objectives The aim of this study was to describe new employees with a recognised disability and compare them to official data and the rest of the workforce. Methods A transversal study was carried out. 149 new employees with recognised disabilities joined a Spanish bank last year, out of 33,190 employees in Spain. Statistical analysis considered variables such as gender, age, workplace location, disability percentage, type of disability, and the need for workplace ergonomic adaptations. Data comparison of the collected data used Pearson's Chi-square test and logistic regression. Results 79% shown mild disabilities, 71% were physical disabilities and 21% were sensory disabilities. 88% didn’t require ergonomic workplace adaptations. Significant differences were found compared to the state's working-age disability statistics: females, under 35 years, locations outside Madrid, physical disabilities, and mild disabilities (p < 0.001). Differences compared to the total workforce included females and those under 44 years (p < 0.001), and locations outside Madrid (p < 0.01). Conclusions Only 12% of new employees with recognised disabilities needed workplace adaptations. The process to integrate workers with disabilities is complex but it is doable. Jobs with few physical requirements are favourable for employees with recognized disabilities. It is easier in young employees, women, workers from outside Madrid, with mild disabilities and physical disabilities.
Keywords: disability; workplace; occupational medicine; occupational health; 25 especially sensitive personnel